Konstribusi Pondok Pesantren dalam Menanamkan Karakter Washatiyah di Yayasan Pondok Pesantren Qamarul Huda Bagu (YP2QH) - Badrun Badrun (PALAPA, 2020)
Islamic boarding schools basically have a distinctive soul and philosophy. This spirit and philosophy guarantees the existence of the pesantren, and even becomes the driving force in educating students and maintaining the continuity of the institution towards progress in the future. The pesantren has five souls or it can be called five souls, namely sincerity, simplicity, independence, ukhuwah / brotherhood, and freedom in determining the field of struggle. As an educational institution, Islamic boarding schools have a big role as a fortress to defend the nation's moral values. However, the decline in moral and ethical values will affect the integrity of the nation and state. Therefore, the government has determined character education as a content that must be present at every level of education, including in Islamic boarding schools.